Continuous quality improvement at the frontline: One interdisciplinary clinical team's four‐year journey after completing a virtual learning program - Claire H. Robinson; Amy J. Thompto; Elizabeth N. Lima; Laura J. Damschroder (Wiley, 2022)
Abstract Background The Veterans Health Administration (VHA) is the largest integrated health system in the U.S. and has identified the learning health system as a strategic priority. Clinicians and staff engaging in active learning through continuous quality improvement (QI) is a key pillar for learning system maturity. An interdisciplinary frontline team at a VHA medical center participated in the Learn. Engage. Act. Process. (LEAP) virtual coaching program to learn how to conduct multidisciplinary team‐based QI cycles of change. These clinicians lead and deliver the MOVE! weight management program, an evidence‐based comprehensive lifestyle intervention. The team worked to continuously improve patient weight loss by engaging in incremental learning cycles of change. The aim of this study is to tell the story of this team's learning experience and the resulting positive reinforcing loop with patient outcomes. Methods This is a mixed methods case study description of one team that participated in the LEAP Program that provides hands‐on QI learning for frontline teams with virtual coaching and a structured curriculum. Autoethnographic qualitative descriptions of team experiences over time illustrate this team's continued engagement in learning loops. Multilevel linear modeling was used to assess patient outcomes before vs after the team's participation in LEAP. Results The team's participation in LEAP provided a set of fundamental QI skills and established a commitment to continual learning. Incremental improvements led to significant weight loss for patients who participated in MOVE! after the team completed LEAP (mean = 9.80 pounds; SD 10.43) compared to the pre‐LEAP time period (mean = −6.83 pounds; SD 9.63). Conclusions Despite competing priorities and time limitations, this team's experiences provide a positive vision of how team engagement in data‐driven continuous learning is feasible at the frontline and can lead to higher job satisfaction and stronger teams. These types of team activities provide much‐needed backbone to being a mature learning health system.